Niveles de fitasa en la alimentación de pollos de carne en la etapa de inicio, crecimiento y acabado. Quevedo - Vera Zambrano, Juan Gabriel (2013)
This research was conducted at the farm The Granite Quininde Located in Canton, km 3 via Esmeraldas - Esmeraldas Province. The geographical coordinates are Latitude 0 ° 43 ¨ 10 "and Longitude 79 ° 33 ¨ 13.20". At an altitude of 85 meters. The experiment lasted 60 days.The used a completely randomized design to see the differences of the means, was used multiple range test of Tukey at 5% probability. They use four levels of phytase at (0.0, 0.015, 0.030, 0.045)% A The 14 days of age, the use of phytase did not improve body weights, weight gains of broilers, showing an average increase 373 g, feed efficiency which showed values of 1.93 and 1.46, while no use was 1.34. At 28 days of age, the best weights and weight gains were obtained with the treatment of 0.015% of phytase (1115 g, respectively), but with the use of 0.030% and 0.045% phytase not reached higher feed conversion the witness was 1.46. at 49 days old, with the use of 0.015% phytase, the birds showed better weight (2852 g), and increased weight (1737 g), and more efficient feed conversions (2.04 to 1.93). The carcass weights were 1.77 kg and 62.44% yields. Depending on the economic analysis, taking into account that there was no mortality and the carcass weight was determined that using 0.015% phytase outperformance was achieved in 7 points, that with the use of the other treatments, and that rates of benefit / cost determined were 1.32 versus 1.25, respectively.